The impact of areas of multiple intelligence on entrepreneurial behavior - Demirel, Erkan T.; Düşükcan, Muhammet; Ölmez, Mehmet (My University, 2012)
The problem addressed by this research is, “do the multiple intelligence skills of entrepreneurs have any impact on their entrepreneurial ideas?” A quantitative research method was employed in this study. The universe of this study is comprised of 880 SME (Small and Medium Size Enterprises) owners operating in Elazig (Turkey). The sample of the study is 212 SME owners participating in the “Small and Medium Industry Development Organization New Support Package Information Meeting” held by the Elazig Chamber of Commerce and Industry on 08.07.2010. One sample t test, correlation test and regression test were used for evaluation of the findings. Research findings indicated that the “multiple intelligence skills of entrepreneurs have a significant decisive impact on their entrepreneurial ideas”.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Multiple intelligence; small and medium size enterprises; entrepreneurial behavior